Firme di artisti / produttori di specchietti in piombo con superficie riflettente in vetro - Baratta, Giulia (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
In this short contribution we present lead mirrors with reflective glass surface that are characterized by the presence of the signature of the plumbarius and / or the creator of the form. These few but interesting epigraphic attestations allow some thoughts on how to produce this type of material and also on the people who were involved.